2010
DOI: 10.1111/j.1728-4465.2010.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Advertising Campaign on Condom Use in Urban Pakistan

Abstract: This study describes an assessment of the impact on condom use in urban Pakistan of the second phase of an intensive condom advertising campaign conducted as part of a social marketing program. Between April and June 2009, advertisements for Touch condoms appeared on private television channels and on radio stations. To assess the impact of the campaign, a nationally representative panel survey of men married to women aged 15-49 was conducted, collecting information on behaviors related to condom use and recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…This highlights the gradual spread of this strategy within public health. We also see the utilization of branding in countries not observed in the 2008 review, including Pakistan [24], Zimbabwe [25], and Spain [40].…”
Section: Community Intervention Trial For Smoking Cessation (Commit) mentioning
confidence: 75%
“…This highlights the gradual spread of this strategy within public health. We also see the utilization of branding in countries not observed in the 2008 review, including Pakistan [24], Zimbabwe [25], and Spain [40].…”
Section: Community Intervention Trial For Smoking Cessation (Commit) mentioning
confidence: 75%
“…For the most part, the campaigns were general family planning/birth spacing campaigns that aimed to increase uptake of modern contraceptive methods and services among men and women of reproductive age. Often campaigns targeted specific sub-groups including women (72%), men (63%), married people (28%), people of low (Bailey, Janowitz, Solis, Machuca, & Sauzo, 1989; Kincaid et al, 1996 ; Singhal & Rogers, 1999 ), middle (Agha & Beaudoin, 2012 ; Agha & Meekers, 2010 ), or high (Foreit, de Castro, & Duarte Franco, 1989 ) socioeconomic status or people of urban (Agha & Beaudoin, 2012 ; Agha & Meekers, 2010 ; Babalola & Brown, 2001 ; Babalola, Vonrasek, Brown, & Traore, 2001) or rural (Singhal & Rogers, 1999 ; Sypher, McKinley, Ventsam, & Valdeaellano, 2002 ) residence. A few campaigns also targeted health workers (Basten, 2009 ; Boulay, Storey, & Sood, 2002 ; Kim, Kols, Nyakauru, Marangwanda, & Chibatamoto, 2001; Palmer & Sood, 2004 ; Shefner-Rogers & Sood, 2004 ), community leaders (Basten, 2009 ; Kim & Marangwanda, 1997 ), and religious authorities (Blake & Babalola, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…This focus of this study has been on factors associated with the intentions to use contraceptives. One recent Pakistani study using panel data has shown a powerful relationship between intentions to use condoms and condom use in a subsequent time period [ 18 ]. Intentions to perform a behavior translate into actual behavior when environmental obstacles can be overcome and individuals have skills to perform the behaviors [ 1 - 3 ].…”
Section: Discussionmentioning
confidence: 99%